Nosarara Nosabatutu: A Culturally Rooted Learning Model in the Midst of a Pandemic - Tandi, Huber Yaspin; Herlina, Herlina; Yuliantini, Yuliantini; Lumuan, Lumuan; Yusuf, Yusuf; Andriyanto, Andriyanto; Antonio, Marites Del Prado (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
The purpose of this study is to develop a Nosarara Nosabatutu learning model based on local culture and technology (Google Docs) to improve the effectiveness of online learning, as well as to assess the effectiveness, validity, and practicality of the model. This research uses research and development (R & D) methods with AP3A (Analyze, Planning, Preparing, Piloting & Apply) model procedures. This second year of research is the stage of developing and testing the effectiveness of the Nosarara Nosabatutu learning model, and is a series of research for 3 years. This second year of research resulted in a model for organizing lecture materials through the google document application, as a component of the Nosarara Nosabatutu learning model. The results of the research product test, both in the one to one test and in the small group test, show that the product in the form of learning materials that have been organized according to the Nosarara Nosabatutu learning model, is in the good category and is effective for improving learning outcomes during the covid-19 pandemic. The material organization model provides independence for students to learn according to their own learning style and pace of learning. This research presents an innovation in the form of integrating the Nosarara Nosabatutu learning model with the Google Docs platform, which combines technology with local cultural values. The impact is that this model not only improves student learning outcomes but also strengthens collaboration and the spirit of mutual cooperation in online learning.